Oil-Induced Land Compensation Dispossession and Women’s Experiences in Albertine Graben, Uganda - Twinamasiko, Specioza; Ahimbisibwe, Frank; Muchunguzi, Charles (Mbarara University of Science and Technology, Uganda, 2018)
In the last thirteen years since the discovery of oil and gas resources in Uganda, numerous developments have taken place to pave way for the development of oil and gas sector which necessitated land acquisition. In response, interventions such as cash compensation, partial land acquisition and resettlement were undertaken. The lacuna for this study is that, there is limited research that focuses on the experiences of women in oil-induced land dispossession, compensation and resettlement in relation to their reliance on the land for livelihood. This paper, therefore, aims at evaluating these experiences on land compensation dispossession for oil and gas development activities and the impact on women‟s livelihoods in Albertine region. A phenomenological study research design was adopted through multimethod such as in-depth interviews, focus group discussions, covert observation and documentary evidence. Purposive sampling was used to select women in categories and snowball sampling to trace displaced women who were not resettled. Findings indicate that cash compensation and resettlement process had loopholes that failed to deal with social, cultural and economic aspects of the affected communities. In conclusion, oil induced compensation process has had devastating experiences on women and many have become more vulnerable. We argue that the negative lived experiences by women as a result of compensation process were attributed to their subordinate status in the rural communities in respect to property ownership and household decision making. The study recommends that future land compensation, resettlement and implementation strategies be gender-inclusive in order to mitigate negative impacts on women livelihoods.
Keywords: Compensation; Dispossession; Livelihood; Oil-induced development